Synergy of Digital Literacy and E-Commerce in Boosting SME Performance - Emi Widiyanti; Cahyadin, Malik; Santoso, Arief Iman; Santoso, Ratna Endah; Widyamurti, Nidyah; Ertimi, Basem (EcceS: Economics, Social, and Development Studies, 2024)
The digital economy (e-commerce) is an important tool to enhance SMEs, with various limitations, including digital literacy and SMEs owner characteristics. The novelty of this study is to provide a deeper understanding and new evidence of the linkage between digital literacy and e-commerce for SMEs. The future expected impact of this study is the government should facilitate and improve the level of digital literacy and e-commerce for SMEs. In particular, this study sets a question, namely: Does technology literacy lead the digital economy (e-commerce) for SMEs? Therefore, this study investigates the determinant factors of e-commerce by moderating variable of digital literacy among SMEs in the Malang region (Malang City, Malang Regency, and Batu City). The sample size is 43 respondents actively involved in business training and mentoring by SME associations, business incubators, and local governments. The respondents have social media and e-commerce to stimulate their sales. The sampling method was purposive sampling. The sample was collected through a survey during March - April 2024. Path analysis was applied to elaborate the study objectives. The findings reveal that the indicators constructing digital literacy and e-commerce are valid and reliable. The digital literacy was influenced by the age of SME owner and economic media. Besides, the digital literacy has a positive and significant impact on e-commerce at the 1% level. E-commerce is also determined by firm establishment. This condition means that an increase in the quality of digital literacy can lead to a rise in e-commerce utilisation. The implications of this study suggest that SME associations, business incubators and local governments facilitate the improvement of SMEs' digital literacy and their ability to utilise e-commerce appropriately to grow their businesses in the long term. In addition, SMEs should improve their digital business skills through various training and business mentoring conducted by local governments and business incubators.